Pemanfaatan Limbah Kulit Buah Nanas dan Jeruk untuk Produksi Eco Enzyme: Uji Fosfor, Kalium, pH, dan TDS - Molsa Vitaloka Putri; Desy Kurniawati; Romy Dwipa Yamesa Away (Lembaga Yasin AlSys, 2025)
The limited research on the use of pineapple and orange peel waste as base materials for eco enzyme production forms the background of this study, despite their high potential as environmentally friendly solutions for organic waste management. This study aims to analyze the characteristics of eco enzyme produced from the fermentation of pineapple and orange peel waste, through phosphorus and potassium tests, as well as measurements of pH and Total Dissolved Solids (TDS). The method employed combines a qualitative approach for phosphorus and potassium testing with a quantitative approach for pH and TDS measurements, using samples from various fruit peel fermentation treatments. The results showed that the resulting eco enzyme had a yellowish-brown, slightly turbid appearance, with relatively high TDS values due to dissolved solid content. The pH values ranged from 3.5 to 4, indicating acidity influenced by organic acids formed during fermentation. Content analysis showed positive results for phosphorus and potassium, supporting its potential use as a liquid organic fertilizer, along with the presence of flavonoids that support its application as a household cleaner or natural disinfectant. The study concludes that pineapple and orange peel waste is an effective and sustainable raw material for eco enzyme production, offering both economic and ecological benefits in household organic waste management.